2001
DOI: 10.1351/pac200173010153
|View full text |Cite
|
Sign up to set email alerts
|

Using neoteric solvents in oil shale studies

Abstract: Abstract:The liquefaction, gasification, and other chemical modifications of oil shale are challenging goals of chemistry and chemical engineering. The use of new solvent systems, such as supercritical fluids and ionic liquids, represents new avenues in the search of environmentally benign technologies. Supercritical fluid extraction (SFE) with carbon dioxide is particularly effective for the isolation of substances of medium molecular weight and relatively low polarity. At elevated temperatures it is possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…The extraction yield and composition from Kukersite oil shale at T ¼ 200 C with water is quite similar to that obtained with methanol-modified carbon dioxide [30]. At supercritical conditions, water can be used for degradation of kerogen, and thus can be used to produce oil from shale.…”
Section: Kerogen Conversion With Supercritical Watersupporting
confidence: 66%
See 1 more Smart Citation
“…The extraction yield and composition from Kukersite oil shale at T ¼ 200 C with water is quite similar to that obtained with methanol-modified carbon dioxide [30]. At supercritical conditions, water can be used for degradation of kerogen, and thus can be used to produce oil from shale.…”
Section: Kerogen Conversion With Supercritical Watersupporting
confidence: 66%
“…At these conditions, the presence of minerals can lead to the formation of additional products. Also, using modifiers to carbon dioxide having a hydrogen-donor capability, like alcohols, lead to hydrogenation reactions [30].…”
Section: Kerogen Conversion With Supercritical Watermentioning
confidence: 99%
“…This is consistent with work by Shi et al [18] which showed that 4.7 wt% of the crude oil was extracted by ethanol. Koel et al also showed that addition of methanol to supercritical CO 2 also led to an increase in the extraction of more polar hydrocarbon-based compounds [32].…”
Section: Characterisation Of Extracted Crude Oilmentioning
confidence: 98%
“…Rather little effects than essential advantages were observed. In [8], solvents of different polarities as methanol, acetonitrile, acetone, methylene chloride, tetrahydrofuran, toluene and hexane were used, and the authors became convinced that the yields of extractables from different oil shales at room temperature were in time lower compared with SEM depending differently on the nature of the solvent. In the same work, dynamic SFE was demonstrated as effective for the isolation of substances of medium molecular weight and relatively low polarity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, in oil shales, dynamic extractions with pure supercritical carbon dioxide in a flow reactor, mainly n-alkanes, were extracted while addition of modifiers as methanol or ionic liquids slightly increased extract yield and enriched its composition with other compounds [8,12].…”
Section: Introductionmentioning
confidence: 99%